De Novo PTEN Mutation in a Young Boy with Cutaneous Vasculitis. (24th April 2017) - Mauro, Angela; Omoyinmi, Ebun; Sebire, Neil James; Barnicoat, Angela; Brogan, Paul
Abstract : Phosphatase and tensin homolog (PTEN) is the protein encoded by the PTEN gene (10q23.3). PTEN mutations are related to a variety of rare diseases referred to collectively as PTEN hamartoma tumor syndromes (PHTS), which include Cowden Syndrome, Bannayan-Riley-Ruvalcaba syndrome, Proteus Syndrome, and Proteus-like syndrome. These diseases are associated with an increased risk of malignancy and for this reason an accurate and early diagnosis is essential in order to institute cancer surveillance. PTEN is a regulator of growth and homeostasis in immune system cells, although there are limited data describing immune dysregulation caused by PTEN mutations. We describe a case of PHTS syndrome caused by a de novo mutation in PTEN detected using a targeted next generation sequencing (NGS) gene panel which was instigated for workup of cutaneous vasculitis. We highlight the diagnostic utility of this approach and that mutations in PTEN may be associated with immune-dysregulatory features such as vasculitis in young children.